Ecos do sistema : reflexos da participação social no processo de licenciamento ambiental - Bentlin, Ana Paula Canedo Arigoni (2021)
This dissertation examines the role of social participation in environmental licensing. The objective of this research is to question whether public hearings in the environmental licensing process contribute to an improvement in the protection of the environment, or if said hearings are just a matter of formal compliance with legal provisions. In the course of this study, a bibliographic review of several renowned authors of sociology, who over the years have contributed directly and indirectly to the environment, was carried out. As a theoretical reference, the analysis utilises Jürgen Habermas’ theory of communicative action, which through his concept of society at two levels (System and Life-world), creates conditions and tools for analyzing the contradictions and possibilities for the defence of the environment within the public sphere. Aspects relating to economic valuation, commercialization and sustainability, forms of participation and the current agenda were analyzed. Further discussion explores the role of FEPAM as an autonomous legal public institution; as well as the plurifunctional and complex processes of environmental licensing - especially when in relation to social participation in public hearings - and its limitations and possibilities of reconciling development with sustainability. The technique used consisted of case studies and interviews. The research includes the analysis of two major licensing processes required of Companhia Celulose Riograndense - CMPC (paper industry, formerly Borregaard) and Votorantim (extraction of lead, zinc and copper, Camaquã Mine), addressing aspects of their application documentation, media coverage, developments and results. Furthermore this dissertation includes a questionnaire completed by employees from the State Foundation for Environmental Protection Henrique Luiz Roessler - RS specialising in this field.